Optimization and Evaluation of Photocatalytic Coatings with TiO2 Nanoparticles for the Elimination of Pathogenic Microorganisms in Critical Environments - Meléndez-Anzures, F. E.; López-Cuellar, E. M.; Martínez-de la Cruz, A.; Contreras-Hernández, L. A. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2026)
Humid indoor environments facilitate the proliferation of microorganisms, posing significant risks to public health. This study focuses on the efficacy of photocatalytic coatings with Degussa P25 titanium dioxide (TiO2) nanoparticles in eliminating Escherichia coli and Staphylococcus aureus under UV irradiation. The aim was not only to demonstrate the effectiveness of these coatings but also to improve the evaluation methodology for future photocatalytic materials. Two methodologies were applied: the glass adhesion method, based on ISO 27447:2009, and a photocatalytic powder test in liquid suspension, adapted from the scientific literature. The results showed a significant reduction in the number of bacterial colony-forming units (CFUs) with the photocatalytic coatings, in contrast to the controls where bacterial concentrations remained constant. Several relevant methodological improvements were implemented, such as extending the range of UV intensities and times, enhancing coating application methods, evaluating variable testing conditions, and optimizing inoculum and photocatalytic suspension distribution. These methodological improvements are crucial for the evaluation of new photocatalytic materials with potential applications in critical environments such as hospitals and schools, thus promoting public health and safety by reducing the spread of pathogens.